Regulator of G-Protein Signaling–5 Inhibits Bronchial Smooth Muscle Contraction in Severe Asthma - Yang, Zhao (American Thoracic Society, 2012)
Severe asthma is associated with fixed airway obstruction attributable to inflammation, copious luminal mucus, and increased airway smooth muscle (ASM) mass. Paradoxically, studies demonstrated that the hypertrophic and hyperplastic ASM characteristic of severe asthma has reduced contractile capacity. We compared the G-protein–coupled receptor (GPCR)–induced Ca(2+) mobilization and expression of GPCRs and signaling proteins related to procontractile signaling in ASM derived postmortem from subjects who died of nonrespiratory causes, with cells from subjects who died of asthma. Despite the increased or comparable expression of contraction-promoting GPCRs (bradykinin B2 or histamine H1 and protease-activated receptor 1, respectively) in asthmatic ASM cells relative to cells from healthy donors, asthmatic ASM cells exhibited reduced histamine-induced Ca(2+) mobilization and comparable responses to bradykinin and thrombin, suggesting a postreceptor signaling defect. Accordingly, the expression of regulator of G-protein signaling–5 (RGS5), an inhibitor of ASM contraction, was increased in cultured, asthmatic ASM cells and in bronchial smooth muscle bundles of both human subjects with asthma and allergen-challenged mice, relative to those of healthy human subjects or naive mice. The overexpression of RGS5 impaired the release of Ca(2+) to thrombin, histamine, and carbachol, and reduced the contraction of precision-cut lung slices to carbachol. These results suggest that increased RGS5 expression contributes to decreased myocyte shortening in severe and fatal asthma.